Chemopreventive Activity of Honokiol against 7, 12 - Dimethylbenz[a]anthracene-Induced Mammary Cancer in Female Sprague Dawley Rats - Wang, Zhenyu; Zhang, Xingyi (Frontiers in Pharmacology, 2017)
Breast cancer is a predominant cause of death in women across the globe. Chemoprevention by using natural, dietary or synthetic products has been appearing to be a fascinating approach to combat the growing burden of breast cancer. In the current study, we intended to explore the mechanisms of chemopreventive action of honokiol against 7, 12 - dimethylbenz[a]anthracene (DMBA)-induced mammary cancer in female Sprague-Dawley (SD) rats. We induced mammary cancer in SD rats by administering single dose of DMBA (80 mg/kg) through intra gastric route. Chemopreventive effects of honokiol (80 mg/kg, i.p) were confirmed from its ameliorating effect on the DMBA-induced anomalies such as liver marker enzymes, Phase I and Phase II metabolizing enzymes and oxidative stress markers. Further, honokiol reversed the DMBA-induced abnormalities in inflammatory cytokines levels and serum tumour markers. Additionally, histopathological examination of mammary tissue and protein expression analysis of NF-κB revealed that honokiol is effective against DMBA-induced mammary cancer. In summary, the results of our study support the chemopreventive feature of honokiol in mammary cancer.